A rare case of hepatic sub capsular biloma after cholecystectomy treated by percutaneous drainage and endoscopic biliary stenting: A case report - Naureen Sameera; Ishaq Aliya; Itu Lizica; Al Awa Arfan; Ghazi Esaaf; Zaid Abdul Aziz; Siddhart Sankar Das; Feras Al Khitab; Syed Javed (Archives of Hepatitis Research - Peertechz Publications, 2019)
Bilomas are localized collections of bile which usually happen post-operatively from an injured cystic or bile duct and most of the biloma collections are in the sub hepatic space. We describe a rare case of hepatic subcapsular biloma after open cholecystectomy which was successfully treated by percutaneous drainage.